American fleet approach Trinidad - (:unkn) unknown (My University, 2011)
This faded postcard, which might be from World War 1, 1914-1918, shows an American fleet approaching Trinidad.
Colour: Sepia; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Warships--United States